The role of a terminal chain in promoting the twist-bend nematic phase: the synthesis and characterisation of the 1-(4-cyanobiphenyl-4′-yl)-6-(4-alkyloxyanilinebenzylidene-4′-oxy)hexanes. Issue 13 (8th December 2018) - Paterson, Daniel A.; Crawford, Catriona A.; Pociecha, Damian; Walker, Rebecca; Storey, John M.D.; Gorecka, Ewa; Imrie, Corrie T.
ABSTRACT: The syntheses and characterisation of the first 10 homologues of the 1-(4-cyanobiphenyl-4′-yl)-6-(4-alkyloxyanilinebenzylidene-4′-oxy)hexanes (CB6O.O m ) are reported. All 10 homologues exhibit nematic, N, and twist-bend nematic, NTB, phases. In addition, an intercalated, anticlinic smectic C, SmCA, phase is observed for m  = 3–5. A second smectic phase is seen for m  = 4, 5 but for which no structural information was obtained. For short chain lengths, the local packing in the nematic phases is an intercalated arrangement. As the chain length increases monolayer fluctuations are observed in both nematic phases. The NTB -N and N-isotropic transition temperatures exhibit a weak odd-even effect as m is increased in which even members show the higher values. This behaviour is accounted for in terms of the change in shape anisotropy and the dilution of the interactions between the mesogenic units on increasing m . The N-I transition temperature falls faster than the NTB -N temperature on increasing m suggesting that the dilution of the interactions between the mesogenic groups has a smaller effect on the shape-driven NTB -N transition than on N-I. Increasing the terminal chain length does not strongly promote smectic behaviour for the CB6O.O m series. This is attributed to the difficulties associated with packing these bent molecules into smectic arrangements. GRAPHICAL ABSTRACT: